Bacillus pumilus isolated from sabkha rhizosphere ameliorates the behavior of the facultative halophyte Hordeum marinum when salt-challenged by improving nutrient uptake and soil health-related traits - Ouissal Metoui-Ben Mahmoud; Rabaa Hidri; Chedly Abdelly; Ahmed Debez (Plant Stress, 2024)
Plant growth-promoting rhizosphere bacteria (PGPR) are increasingly considered as highly efficient bioagents. They confer for instance better salt tolerance to host plants while improving soil enzyme activities and microbiome diversity, which are indicators of soil biological health and fertility. Here, the aim was to investigate the efficiency of native bacteria from saline rhizosphere of Hordeum marinum, in alleviating the adverse effects of salinity in this facultative halophyte with fodder potential. Following identification and characterization for salt tolerance capacity and in vitro plant growth promoting potential, the bacteria strain Bacillus pumilus, was selected for its ameliorative effects on H. marinum when cultivated under NaCl salinity (200 mM) in a greenhouse experiment. Salinity significantly restricted growth, induced oxidative stress and disturbed the mineral nutrition of H. marinum, whereas inoculation with B. pumilus significantly restored growth, as leaf elongation rate and plant dry weight. Similarly, the highest accumulation of K+, N and P were observed in inoculated plants challenged with salinity. This was concomitant with reduced MDA and H2O2 levels, thereby preventing oxidative damage in H. marinum plants cultivated under salt stress. Furthermore, B. pumilus strain also overcame salt impact via indirect mechanisms by activating soil enzymes (dehydrogenase, β-glucosidase and acid phosphatase) and microbial biomass C production. Overall, our data further highlight the environmental significance of microorganisms inhabiting extreme environments like sabkhas as promising agents for biological approaches aiming at saline soil rehabilitation and improving plant productivity when challenged with salinity, due to their beneficial effect on both plant and the rhizosphere.